Generalization of the Lidskii theorem on the localization of the spectrum of a product of Hermitian operators - Shvartsman, P. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider productsC=AB of Hermitian operators in ann-dimensional unitary space. Two equivalent localization theorems are proved in the case where one of the factorsA andB is positive definite.